VLOG-BASED EFL TEACHING MODEL FOR UNIVERSITY STUDENTS: IMPACT ON SPEAKING SKILLS AND ENGAGEMENT - Zhang, Mingxia; Wu, Changhua (PUPIL: International Journal of Teaching, Education and Learning, 2024)
This study aims to investigate the efficacy of a vlog-based teaching model in enhancing oral speaking skills and engagement among university students in an English as a Foreign Language (EFL) setting. With the digital technologies reshaping educational methodologies, this research integrates vlogs (video blog) into EFL teaching to build a more engaging learning path. The study was conducted over a semester with 30 university EFL learners in China, employing a mixed-methods approach to evaluate the impact of vlog-based learning. Pre-and-post oral speaking tests were administered to assess improvements in students' language proficiency, while questionnaires measured levels of engagement and motivation. Initial findings suggest that the vlog-based teaching model significantly improved students' speaking skills and heightened their engagement in learning English, indicating a promising avenue for digital media integration in language education. This paper contributes to the evolving field of digital media in EFL teaching, offering insights into the potential of vlogs to enrich language learning experiences and outcomes.